(untitled) (Nóema, 2015)
Relazione presentata al Seminario di Filosofia Teoretica nella primavera 2015. Given the topic of the given, it would be all too easy to become entangled in highly technical disputes about Wilfrid Sellars, John McDowell, and other authors regarding how to interpret and, then, assess, their critiques of “myth of the given.” Though I am dubious whether we could within the limits of this articlemove toward resolving any of these questions, such an engagement might nonetheless prove profitable. It would also likely prove to be invigorating, since wrestling with technical issues in a systematic manner carries a unique form of intellectual enjoyment for the properly trained philosopher. Even so, that is not my intention today. Rather my aim is simply to sketch, mostly in broad bold strokes, though to some extent also in minute, careful ones, what I take to be a pragmatist approach to this multifaceted controversy. In my judgment, much still depends upon coming to a deeper appreciation of one of the central lessons of the pragmatist movement: the recurrent need to articulate a more truly empirical understanding of human experience. Above all else, then, my reflections aim at deepening the contemporary appreciation of the pragmatist take on human experience.